A multi-centre, participant-blinded, randomized, 3-year study to compare the efficacy of Virtual Surgical Planning (VSP) to Freehand Surgery (FHS) on bony union and quality of life outcomes for mandibular reconstruction with fibular and scapular free flaps: study protocol for a randomized phase II/III trial - Khanh Linh Tran; Sena Turkdogan; Anat Bahat Dinur; Thomas D. Milner; Edward Wang; Anthony Nichols; Danielle MacNeil; Adrian Mendez; Jake Jervis-Bardy; John De Almeida; Christopher Yao; David Goldstein; et al. (BMC Cancer)
Abstract Background Advanced head and neck malignancies with underlying bony involvement often require aggressive oncological resection of large segments of the oral cavity including the mandible. These patients require vascularized donor osseous free tissue transfer to reconstruct significant defects. Traditionally, the donor bone is harvested on its vascular supply and shaped to the defect in a free hand fashion (FHS). However, virtual surgical planning (VSP) has emerged as a method to optimize reconstructive outcomes and decrease operative time. The goals of this study are to assess superiority of VSP to FHS by comparing bony union rates at 12 months, short and long-term complication rates, reconstruction accuracy, quality of life (QOL), functional outcomes, and economic analysis. Methods This is a multicenter phase II/III study randomizing four hundred twenty head and neck patients undergoing mandibulectomy in a 1:1 ratio between VSP and FHS. Intention-to-treat analysis will be performed for patients enrolled but unable to undergo VSP-aided reconstruction. The primary endpoint is bony-union rates at 1 year post-operatively. Secondary outcomes include complication rates, QOL, functional outcomes, and economic burden. Discussion This study will provide an assessment of two different surgical approaches to the reconstructive methods of mandible defects using fibular or scapular free flaps on bony-union rates, complications, QOL and economics. Trial registration Clinicaltrials.gov identifier: NCT05429099. Date of registration: June 23, 2022. Current version: 1.0 on March 6, 2024.